AN ASSESMENT OF STUDENTS’ MASTERY OF ENGLISH PRONOUNS: A CASE STUDY - Nur, Asniar U.M; Anwar, Indry Widyasti; Octasary, Magvirah (Jurnal Bilingual, 2025)
This study aims to assess the ability of Grade VIII-1 students at Al-Irsyad Junior High School, Ternate City, in using English pronouns during the 2025 academic year. Using a descriptive qualitative approach, data were collected from 42 purposively selected students through a test consisting of 10 multiple-choice and 20 essay questions. Results showed that only one student reached the excellent category, 45.23% were in the good category, 14.28% in the fair category, and 38.09% also classified as fair. The average score was 54.66, indicating a generally low level of proficiency, largely due to students’ difficulty distinguishing between subjective and objective pronouns.